Rehabilitation with Five Osseointegrated Implants in an Atrophic Maxilla: A Case Report - Lima, Bárbara Nathalia Marques de; Costa, Maria Taywri Almeida; Almeida, Vilmar Santos de; Carvalho e Silva, Raphael; Barros, Mauro Luiz Travessa de; Ferreira, Francisco Amadis Batista; Silva Junior, José da (Brazilian Journal of Case Reports, 2025)
Tooth loss is a public health issue in Brazil, impacting nutrition, speech, aesthetics, and self-esteem. Implant-supported prostheses are considered the gold standard for replacing missing teeth. Bone resorption, a consequence of tooth loss, can lead to an atrophic ridge, making implant treatment more challenging. This paper reports a case of rehabilitation with a fixed full-arch prosthesis supported by five implants in an atrophic maxilla. The patient sought care at the RC Institute of Postgraduate Dentistry to replace her removable maxillary prosthesis with a fixed, implant-supported one. Imaging exams revealed an atrophic maxilla with reduced bone width and limited height in the posterior region due to maxillary sinus pneumatization. Surgery for the placement of five implants was performed with proper distribution and angulation. Three months after surgery, with the implants osseointegrated, the prosthetic phase began, and treatment was completed with the installation of a porcelain fixed full-arch prosthesis. The use of angled implants proved to be an excellent alternative, allowing the placement of long implants, reducing the distal cantilever, and avoiding invasive procedures. This resulted in lower morbidity, shorter treatment time, and reduced costs.